Perlindungan Data Pribadi Mengenai Kebocoran Data Dalam Lingkup Cyber Crime Sebagai Kejahatan Transnasional - Silalahi, Putri Hasian; Dameria, Fiorella Angella (Universitas Batanghari Jambi, 2023)
In this era of globalization, internet technology is growing rapidly from time to time. The right to privacy data is part of the privacy rights inherent in every individual. Until now the internet can be used as a new tool to commit a crime, especially cyber crime. The network is broad and can break through the barriers of national borders, enabling the occurrence of a cyber crime that can be carried out by crossing national borders or better known as transnational crime. This cyber crime can cause great losses both material and non-material. Moreover, cyber crime that is transnational in nature makes cyber crime require special treatment to handle it. Indonesia carried out two handlings both externally and internally. Externally, Indonesia and the National Police cooperate with the Australian Federal Police. Meanwhile, internally Indonesia formed institutions such as Id-SIRTII, Trust+positive, the birth of the European Union Convention On Cybercrime Bill, Cyber Defense Competition, Development of Cyber Defense. External handling is carried out by the Indonesian government to overcome Cyber crime that is across national borders.